(untitled) (Journal of Libya for geographical studies, 2026)
This study examines the potential for flash flood harvesting in the Wadi Tifalghu basin using remote sensing techniques and Geographic Information Systems (GIS), with the aim of identifying flood hazards within the basin and assessing possibilities for mitigating their impacts. The drainage basin covers an area of approximately 2,059 km². The study area is dominated by geological formations dating back to the Upper Cretaceous period, which account for about 93.5% of the basin and represent the most extensively exposed formations. The elevation of the basin surface ranges from 234 m at its outlet into Wadi Souf Al-Jeen to 952 m above sea level in the upper parts of Jabal Nafusa between Gharyan and Al-Asabi‘a, with a significant elevation difference of about 718 m and a gradual transition in elevation between these points. Basin slopes vary from 0° to 40°. With regard to slope aspect, the dominant direction is southward (14%), followed by southeast (13.9%), east (13.8%), and southwest (13%). These slope directions play a major role in controlling the direction of surface runoff generated by rainfall. The prevailing soils in the basin consist mainly of loamy soils mixed with medium- to coarse-grained materials, covering about 99.7% of the area, while sandy clay soils occupy only 0.3%. The study identified six land-cover classes, with shrubs occupying the largest proportion of the basin area (96.1%). The results indicate that the application of water harvesting techniques in the basin is feasible. Accordingly, several suitable sites were proposed for the construction of dams to store rainwater and reduce the risks associated with flash floods.